Study on Ohmic Heating Behavior of Fly Ash Filled Carbon Woven/Epoxy Resin Composite (Journal of Fiber Bioengineering and Informatics, 2023)
The Ohmic heating behavior and electrical property of the carbon fabric/green epoxy composite laminatesfilled with various concentrations of unmilled fly ash and milled fly ash were investigated in presentwork. We used an infrared camera to record the change in surface temperature of composites over aperiod of time by varying the voltage from 0 to 10 V. The results show that the composite containinglow concentration of fly ash exhibited the optimum Ohmic heating behavior under different appliedvoltages. The maximum temperatures of epoxy/carbon composites were adjustable by controlling theconcentrations of fly ash fillers as well as the applied voltage. When a certain voltage was applied tothe composite, the surface temperature of composite raised to the maximum within 20 s and becamestable, then cool down to room temperature in 120 s. In addition, the milled fly ash filled epoxy/carboncomposites were found to reveal improvement in electrical heating performance and structural stabilityover the unmilled fly ash filled composites.
Keywords: Ohmic Heating; Fly Ash; Carbon Woven; Composite Laminates